Sistema de alto desempenho para compressão sem perdas de imagens mamográficas - Marques, José Raphael Teixeira (2010)
The usage of mammographic image databases in digital form and the practice of telemedicine require to store and to transmit large amounts of data. The image digitization from a single mammographic exam with appropriate resolution can take up to 120MB of space in disk, which becomes even more critical when considering the large number of exams per day on a clinic. Thus, efficient data compression techniques are needed to reduce storage and transmission costs. This document describes the development of a high-performance lossless compressor based on Prediction by Partial Matching (PPM) algorithm with modules for segmentation, mapping, gray code, bit planes decomposition and move-to-front transform, for mammographic image compression. The compressor developed was efficient in both compression ratio and processing time, and compresses 27MB images in about 13 seconds with an average compression ratio of 5,39.